2021
DOI: 10.22201/fpsi.20074719e.2021.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Condiciones Socioeconómicas y de Salud Mental durante la Pandemia por COVID-19

Abstract: El objetivo del trabajo fue describir el nivel de riesgo a la salud mental en función de las condiciones socioeconómicas y las relacionadas con la pandemia por COVID19. Se trabajó con 15,335 personas mexicanas, (M= 26 años, DE=11.95), 52% solteras (8,001), 60% mujeres (9,175), 44% en cuarentena (6,769). Se utilizó un estudio correlacional causal exposfacto utilizando la WebApp para la detección de riesgos a la Salud Mental COVID19 (Alfa de Cronbach de 0.96; varianza explicada del 62%) programado con Linux®, PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 14 publications
1
5
0
5
Order By: Relevance
“…Participants who reported COVID-19 status also reported high levels of generalized anxiety symptoms. These findings are very similar to those reported by Morales-Chainé et al (2021b). Moreover, in the present study, we also found that those who seek psychological care reported high levels of generalized anxiety, intrusion, hyperactivation, and health anxiety symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Participants who reported COVID-19 status also reported high levels of generalized anxiety symptoms. These findings are very similar to those reported by Morales-Chainé et al (2021b). Moreover, in the present study, we also found that those who seek psychological care reported high levels of generalized anxiety, intrusion, hyperactivation, and health anxiety symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…In the sixth step, we undertook means, standard deviation, multivariate analysis, and return to Cohen's d effect analysis to consider such means comparison of the dimensions with the whole sample. Finally, we integrated an overall model, including the prediction between latent variables via a chi-square test and their fit indices through structural equation modeling (SEM; Morales-Chainé et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations